THEORETICAL-METHODOLOGICAL ASPECTS OF LANDSCAPE PLANNING - Viktoriia Udovychenko (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2015)
Landscape planning definition is carried out in this article. The key features of landscape planning as an essential part of spatial planning are analyzed. Objects of landscape planning, which need to be taken into account, were defined in this article. Moreover, the main directions of landscape planning realization are explained. The key territorial levels of landscape planning are under consideration in this article and the variety of territorial units and range of scales for each level of landscape planning are shown.